Analysis of Green Finance , Excellent Service Quality (ESQ), and Corporate Social Responsibility (CSR), on Hospital Values in Lamongan Regency - Nur Kumalasari, Aprilia; Dwi Hartantyo, Sugeng (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
Hospital value reflects the quality, benefits, and impacts that the hospital provides to the community, both in terms of health services, operational management, and social contributions. This value can be measured from various indicators, such as medical service quality standards, financial management efficiency, patient satisfaction levels, and roles in improving public health. This study discusses the influence of green finance , excellent service quality , and customer social responsibility. with the aim of assessing the value of hospitals in Lamongan district with the criteria of hospitals that have been accredited as superior . The research method used is a quantitative research method using the SEM PLS analysis tool . The results of the study indicate that green finance has a significant effect on hospital value . In addition, Excellent service quality also has a significant effect on hospital value, providing insight into quality service on hospital value, and Customer Social responsibility has a significant effect on hospital value. Thus, this study contributes to hospital financial management, as well as providing recommendations for hospitals, related agencies, in implementing the results of this study. However, this study has several limitations, which can be a reference for further research.